Increasing Interdisciplinary Relationship Of History Teaching And Effective Use Of Information Technology Tools (Eurasian Journal of Learning and Academic Teaching, 2024)
In this article, it is proposed to increase the interrelationship of history teaching with other subjects, the effective use of modern technology tools in the formation of better understanding and memorization of the educational material, and students' work with information technologies. A wide range of opinions and considerations regarding the systematic organization of skills are discussed and fully explained.